ChemInform Abstract: Hydrothermal Liquefaction (HTL) of Microalgae for Biofuel Production: State of the Art Review and Future Prospects. Issue 16 (22nd April 2014) - Lopez Barreiro, Diego; Prins, Wolter; Ronsse, Frederik; Brilman, Wim
Abstract Review: 76 refs.